Badges for all: using gamification to engage HCI students - Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Keeping students attentive and participative is a challenge in the context of higher education. Considering the computing field, its inherent complexity, alongside a scenario where the classes are at night, engagement is even more challenging. To deal with these issues, several methodological alternatives have been discussed, including gamification. Trying to promote student engagement, we used a set of 15 distinct badges, related to different kinds of activities (individual, in groups, at home, in class, among others), in an HCI undergraduate course, with 46 students, during an entire semester. We collected data about earned badges, user satisfaction, as well as their grades and class attendance. Our main results are related to the students’ engagement and satisfaction, adding new evidence of the gamification effectiveness in the educational context, as well as its possibilities of use in an HCI course.